2005
DOI: 10.1002/dmrr.573
|View full text |Cite
|
Sign up to set email alerts
|

Life course determinants of insulin secretion and sensitivity at age 50 years: the Newcastle thousand families study

Abstract: Insulin secretion is largely unexplained by these data. For insulin resistance, the evidence suggests a limited impact of early life and a larger impact of adult factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…While this would have been a potential explanation for an inverse association between duration of breastfeeding and cholesterol levels, it would not appear to be a likely explanation for the sex differences seen in this study. Previous research using this cohort has found duration of breastfeeding to be negatively associated with HOMA insulin resistance in men, but not in women [7] and to be associated with reduced seroprevalence of Helicobacter pylori in men, but not in women [22].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…While this would have been a potential explanation for an inverse association between duration of breastfeeding and cholesterol levels, it would not appear to be a likely explanation for the sex differences seen in this study. Previous research using this cohort has found duration of breastfeeding to be negatively associated with HOMA insulin resistance in men, but not in women [7] and to be associated with reduced seroprevalence of Helicobacter pylori in men, but not in women [22].…”
Section: Discussionmentioning
confidence: 94%
“…A large number of epidemiological studies have suggested an association between birth weight and growth in early life and the risk of adverse health outcomes such as cardiovascular disease and diabetes in later life [3], although the extent to which early life factors explain variations in risk varies between studies and leaves much heterogeneity in risk unexplained [4][5][6][7] It has also been proposed that lipid metabolism is 'programmed' by factors, such as birth weight and infant feeding, that operate very early in life. In particular, a number of studies have suggested that prolonged breastfeeding is associated with decreased levels cholesterol in adulthood [8].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…If this is a real difference, then it may go someway towards explaining sex differences in the associations between markers of fetal growth and metabolic outcomes in later life [17, 18]. Clinical parameters such as associations with hirsutism and irregular menses might suggest that the metabolic syndrome occurs more frequently in females than males, but biochemical indices such as insulin resistance are ultimately more profound in males [17, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…11 Complete data in infancy and on clinical measurements were available for 408, of whom 27 (19 female) had at least one episode of diarrhoea recorded in infancy. Dietary sodium intake at the age of 50 years was available for 398, including all of those with an episode of diarrhoea recorded in infancy.…”
mentioning
confidence: 99%